Professional Formation as an Inter-subjective Social Phenomenon: the perspective of Alfred Schutz (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Alfred Schutz, upon developing his work, he did not use his theoretical postulate in Professional Formation. Nevertheless, the distinction the author makes in the study of the inter-subjective social phenomenon,  and its approaches about the notions of ”daily life”  and “ scientific world”  help us consider some elements that participate epistemologically in the phenomenon of the Professional Formation.  His postulate about the “ theory of the motives”,  especially when considering the OTHER and the United projects of actions help us initiate an analysis and interpretations about the complexities and importance that Professional Formation  has.
Keywords: education; Schutz; Profesional Education; daily life